ANALISIS NILAI KALOR BERBAHAN BAKAR BIOGAS DENGAN MEMANFAATKAN KOTORAN SAPI KALOR BERBASIS ETNOSAINS - Ulva, Siti Maria; Damayanti, Puardmi; S. Abd. Syukur , Muh. Syarif (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
Abstract This study aims to obtain the calorific value of biogas produced from cow dung and know how to use the application of cow dung as biogas fuel in the village of Gunung Putih based on ethnoscience. This type of research uses experimental method by preparing the main ingredients of cow dung for processing in the manufacture of biogas based on ethnoscience. At the data gathering stage using the manometer gauge and the Black Principle method. The process of data analysis performed there are 3 steps, that is calculate: (1) gas pressure produced by using U manometer, (2) value of temperature change (ΔT) in water hence obtained amount of heat needed, (3) report result of measurement Physical quantities can name X = (x0 ± Δx). The results showed that the measured results were X = (282,98 ± 35,60) J / kg. To find out how to use biogas in Gunung Putih Village, the farmers in the village cow manure process into a reactor with fixed domed plant type. In the process of making biogas, the amount of cow dung and water used is with a ratio of 1: 1.5. The product of this research can be used as teaching material in applied physics courses.